Ethnobotanical study of medicinal plants used by the people of Mosop, Nandi County in Kenya - Maiyo, Z. C.; Njeru, S. N.; Toroitich, F. J.; Indieka, S. A.; Obonyo, M. A. (Frontiers in Pharmacology, 2024)
The study documented the diversity of medicinal plants used by the community of Mosop in Nandi-Kenya and gathered data from traditional medicine practitioners about the different parts used and the most effective way to administer them. Utilizing statistical methods, this study shows the relationship between the identified disease categories and the medicinal plant species used by determining the quantitative relevance of the data collected using a variety of indicators. The results show the diversity and richness of 253 species of medicinal plants spanning 74 families. The medicinal plant species that have been used to treat specific infectious and parasitic disease categories have the most use reports. The wealth of information from the study will encourage further phytochemical and pharmacological investigations that may result in the development of potentially significant pharmaceuticals. Global warming is having an increasing impact on biological richness, thus the world will have to deal with its effects as they become more obvious. The results, in our opinion, will be of interest to environmental conservationists who are trying to support biodiversity through initiatives such as the in situ establishment of medicinal plant gardens at particular sites in collaboration with the local population.